World Hypertension Day 2024 and unveiling the hidden challenge: Endocrine hypertension (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Abstract not availableJ Assoc Clin Endocrinol Diabetol Bangladesh, July 2023;3(2): 38-39